Addressing racism in the workplace through simulation: So much to unlearn - Fricke, Moni; Beach Ducharme, Debra; Beavis, Allana; Flett, Priscilla; Oosman, Sarah (Frontiers in Rehabilitation Sciences, 2023)
Introduction Racism exists in the healthcare system and is a root cause of health inequities among Indigenous Peoples. When microaggressions of racism are carried out by healthcare providers, therapeutic trust may be broken and quality of care may be impacted. Anti-racism response training is considered best practice in recognizing and addressing racism. The objective of this study was to evaluate the impact of a virtual (synchronous) anti-racism response training workshop among a group of rehabilitation therapists from across Canada. Methods A 90-minute virtual anti-racism simulation workshop for rehabilitation therapists was developed and delivered virtually four times across Canada between 2020 and 2021. Following an introduction and pre-briefing, role-playing among participants was used to address microaggressive Indigenous-specific racism, followed by an in-depth debriefing with trained facilitators. A post-workshop survey was conducted to evaluate this anti-racism simulation workshop and assess the impact on participating occupational therapists (OTs) and physiotherapists (PTs). Following each simulation workshop, participants were invited to complete an anonymous post-activity survey (n = 20; 50% OTs, 45% PTs). Open text responses were analyzed thematically from the perspective of critical race theory. Results The majority of the participants self-identified as women (95%); white (90%); mid-career (52%); and had never personally experienced racism (70%). All participants agreed that the workshop gave them ideas on how to start dismantling racism in their workplace. Thematic analysis resulted in four themes: so much to unlearn, remain humble, resist the silence, and discomfort is okay. Discussion Despite feelings of discomfort, OTs and PTs appreciated anti-racism skills-based training and recognized the importance of taking action on racism in the workplace. Findings from this study support online (synchronous) anti-racism training as a viable and effective means of creating space for rehabilitation professionals to lean into brave conversations that are necessary for developing strategies to address racial microaggressions impacting Indigenous persons in the workplace. We believe that these small steps of preparing and practicing anti-racism strategies among rehabilitation therapists are essential to achieving a collective goal of dismantling racism in the health system.